Simulation of an adaptive controller for a limited-bandwidth active suspension. (29th October 2004) - Ramsbottom, M.; Crolla, D.A.
Mathematical modelling and computer aided simulation techniques have been used to develop an adaptive control scheme for an active vehicle suspension system. The proposed scheme comprises a variant of the self-tuning pole-assignment algorithm. The active suspension problem is interpreted as one of regulation and setpoint tracking, and as a consequence, combined ride and levelling control is realised. Simulation results for a quarter vehicle model indicate that ride performance benefits can be achieved in parallel with levelling control capabilities. Moreover, it is shown that this scheme retains good control performance even in the presence of vehicle configuration uncertainties and road disturbance changes.